2021
DOI: 10.1371/journal.pone.0249552
|View full text |Cite
|
Sign up to set email alerts
|

Recipient pre-existing chronic hypotension is associated with delayed graft function and inferior graft survival in kidney transplantation from elderly donors

Abstract: Background Pre-existing chronic hypotension affects a percentage of kidney transplanted patients (KTs). Although a relationship with delayed graft function (DGF) has been hypothesized, available data are still scarce and inconclusive. Methods A monocentric retrospective observational study was performed on 1127 consecutive KTs from brain death donors over 11 years (2003–2013), classified according to their pre-transplant Mean Blood Pressure (MBP) as hypotensive (MBP < 80 mmHg) or normal-hypertensive (MBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Further analysis of 18 paired grafts in different recipients (hypotensive vs. nonhypotensive) showed that the odds of DGF were 7 times higher compared with normotensive pairs. Pretransplant hypotension was also shown to be associated with perioperative hypotension and perioperative fluid administration of >3 L. 1 In our study, the vasopressin group received significantly less net fluid compared with no-vasopressin groups but ended up with a nonsignificant higher net positive fluid status in the first 24 hours post-DDKT owing to significantly less urine output (2.3 L vs. 4.6 L, P < 0.0001).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Further analysis of 18 paired grafts in different recipients (hypotensive vs. nonhypotensive) showed that the odds of DGF were 7 times higher compared with normotensive pairs. Pretransplant hypotension was also shown to be associated with perioperative hypotension and perioperative fluid administration of >3 L. 1 In our study, the vasopressin group received significantly less net fluid compared with no-vasopressin groups but ended up with a nonsignificant higher net positive fluid status in the first 24 hours post-DDKT owing to significantly less urine output (2.3 L vs. 4.6 L, P < 0.0001).…”
Section: Discussionmentioning
confidence: 45%
“…A study from Dolla et al. 1 looking at pretransplant hypotension showed that the odds of DGF were 4.5 times higher with mean BP <80 mm Hg. Further analysis of 18 paired grafts in different recipients (hypotensive vs. nonhypotensive) showed that the odds of DGF were 7 times higher compared with normotensive pairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the occurrence of intraoperative hypotension was slightly higher in the KT and LT groups compared with the nontransplantation group. As a higher risk of delayed graft function secondary to a hypotension‐mediated reduction in renal blood flow was reported previously, 50 the impact of intraoperative hypotension on kidney function might be higher in kidney transplant recipients. Therefore, team‐based approach, including an anesthesiologist, a nephrologist, and a surgeon, in order to avoid intraoperative hypotension during hip fracture surgery, will be important for better outcomes, particularly in KT transplant recipients.…”
Section: Discussionmentioning
confidence: 52%
“…Most transplant recipients in the study were Caucasian and Black, limiting the generalizability of our findings. As with other retrospective studies, our analysis may be confounded by variables that were not included in our models, such as blood loss, kidney allograft size, perioperative hypotension [ 24 ], proteinuria or nephrotic syndrome, and immunosuppressant choice and level. Our follow-up was only one year.…”
Section: Discussionmentioning
confidence: 99%